Advancing cross-disciplinarity in bone and joint infection science using the COMBINE approach: an example from Denmark - L. K. Jensen; T. Bjarnsholt; T. Bjarnsholt; H. Gottlieb; M. Bue; M. Bue (Journal of Bone and Joint Infection)
In 2018, the Centrum fOr translational Medicine on Bone and joint INfEctions (COMBINE) was created to facilitate collaboration among Danish scientists and researchers dedicated to bone and joint infection research. The COMBINE approach was developed to ensure successful collaboration, and this publication aims to share this successful approach.